Effective Drill-Based Arithmetic Training for Improving Numeracy Literacy: A Quasi-Experimental Study With High N-Gain among Elementary Students - Safiru Hunas; Eva Puspitasari; Rama Wijaya Abdul Rozak; Nandang Rusmana (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to analyze the effectiveness of a drill-based arithmetic training program in improving elementary students' numeracy literacy. Methodology: This quasi-experimental one-group pretest-posttest study involved 32 fourth-grade students selected through a total sampling approach. A 20-item arithmetic essay test was used as the instrument (CVR = 0.89; Cronbach's Alpha = 0.856). The intervention comprised 8 sessions (90 minutes each) integrating drill and practice, concrete manipulative media, scaffolding, peer tutoring, and corrective feedback. Data were analyzed using the Wilcoxon Signed-Rank Test (α = 0.05) and Hake's N-Gain. Main Findings: Pretest scores were extremely low (M = 15.31), with 0% achieving KKM (Minimum Completion Criteria). Post-intervention scores rose to M = 82.03, a gain of 66.72 points (435.71%), with 84.4% of students achieving KKM. The Wilcoxon test confirmed a highly significant improvement (p = 0.000001), and N-Gain yielded a mean of 0.7964 (high category). Effectiveness is attributed to the integration of drill-and-practice (behavioristic theory), concrete manipulatives (Piaget), peer tutoring within the Zone of Proximal Development (Vygotsky), and gradual scaffolding. The N-Gain exceeded prior studies. Limitations include the absence of a control group and a small sample size, restricting generalizability. Novelty/Originality of this study: This is the first study to examine an integrated, multi-component program that addresses all four arithmetic operations simultaneously in Eastern Indonesia (Buton Regency), demonstrating that multi-component designs yield superior N-Gain outcomes and offering a replicable framework for teachers addressing low numeracy literacy.